Effects of endurance exercise and dietary protein intake on osteokine, bone turnover, and inflammatory markers in endurance runners: A narrative review - Sofia Valente Ferreira; Silar Gardy; Tyler A. Churchward-Venne; Andrea R. Josse; Jenna C. Gibbs (Bone Reports)
Bone stress injuries are pervasive among endurance runners due to repetitive sport-specific mechanical loading and a higher prevalence of low energy availability (i.e., inadequate dietary energy intake relative to exercise energy expenditure). Chronic endurance exercise promotes bone formation, thus, runners typically have higher bone mineral density (BMD) than non-weightbearing athletes and sedentary individuals. However, runners may experience increased bone resorption for hours to days following an endurance exercise bout. If recovery is insufficient, uncoupled bone turnover can pose a significant risk to their bone health. While skeletal-immune system crosstalk has been studied, the interaction during and after exercise in athletes is an emerging area of research. Nutritional interventions have been investigated for their effects on bone metabolism surrounding exercise. However, limited research has examined dietary protein intake in endurance athletes, particularly concerning its effects on bone metabolism and osteoimmunology. This narrative review provides an overview of the evidence on the effects of endurance exercise and dietary protein intake on osteokines, bone turnover, and inflammatory markers in endurance athletes. Acute bouts of high-intensity running increase osteokines and bone turnover markers that promote bone resoprtion which parallels increases in pro-inflammatory markers in endurance athletes, suggesting crosstalk between these systems during and after exercise. Chronic endurance exercise promotes increased resting levels of bone formation, while reducing resting pro-inflammatory markers. Adequate dietary protein ingestion habitually and pre-, during, and post-exercise may attenuate bone resportion and pro-inflammatory markers in endurance athletes.